Research method for determining phyllite fracture surface roughness and destruction mode based on digital three-dimensional reconstruction
Through the research method based on digital three-dimensional reconstruction, the problem of difficult prediction of the shear failure characteristics and fracture surface roughness of Qianmei rock under different stress conditions was solved, and the precise quantitative characterization and relationship model of the fracture surface roughness and failure mode of Qianmei rock was realized, which improved the scientificity and safety of engineering design.
Patent Information
- Application Number
- CN202411801039.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to accurately predict the shear failure characteristics and cracking surface roughness of Qianmei rock under different stress conditions, resulting in safety hazards and increased costs in engineering design and construction.
Using a research method based on digital three-dimensional reconstruction, we use a research method to collect and determine the physical properties of Qianmai rocks, conduct uniaxial compression and direct shear tests, simulate fracture characteristics using PFC numerical models, acquire fracture surface point cloud data in combination with three-dimensional laser scanning, analyze two-dimensional and three-dimensional roughness, determine the relationship between fracture surface roughness and stress, and comprehensively destroy the pattern.
The precise quantitative characterization and relationship model of the roughness and failure mode of Qianmei Rock was realized, which improved the understanding and prediction ability of Qianmei Rock's mechanical behavior, and enhanced the scientificity and safety of engineering design.
Smart Images

Figure CN119574309A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rock mechanics and geological engineering technology, and in particular to a research method for determining the roughness of a phyllite fracture surface and a failure mode based on digital three-dimensional reconstruction. Background Art
[0002] As a common soft rock, phyllite has complex physical and mechanical properties and has an important impact on many engineering fields such as tunnel excavation and slope stability. In actual engineering, the shear failure characteristics of phyllite and the relationship between the roughness of the fracture surface and stress are not fully studied. Previous studies have focused on the determination of a single mechanical parameter or simple observation of failure morphology, lacking a systematic study of the characteristics of phyllite from microstructure to macroscopic fracture surface during shear failure under different stress conditions, especially in the quantitative characterization of shear surface roughness and stress relationship, and have failed to establish a complete and accurate model. This research status makes it difficult to accurately predict the mechanical behavior and stability of phyllite during engineering design and construction, which may cause engineering safety hazards and increase engineering costs.
[0003] As engineering construction expands into complex geological environments, it becomes necessary to deeply explore the relationship between the roughness of the shear fracture surface of phyllite and stress. On the one hand, modern engineering requires higher precision in rock mass stability analysis, which traditional research methods can no longer meet; on the other hand, the development of new measurement technologies and analysis methods has made it possible to comprehensively and deeply study the characteristics of phyllite, prompting researchers to conduct more detailed and in-depth exploration of the mechanical behavior of phyllite.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] The purpose of the present invention is to provide a research method for determining the roughness and failure mode of the fracture surface of phyllite based on digital three-dimensional reconstruction, so as to solve the problems mentioned in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides a research method for determining the roughness and failure mode of the fracture surface of phyllite based on digital three-dimensional reconstruction, comprising the following steps: S1: collecting a specific phyllite rough stone processing sample; S2: measuring the physical properties of the phyllite test; S3: measuring the uniaxial compressive strength of the phyllite test;
[0007] S4: Observe the uniaxial compression failure process of rock through a high-speed camera; S5: Establish a numerical model of uniaxial compression test of rock through PFC and analyze the rock fracture characteristics; S6: Use a microcomputer to control the rock direct shear instrument to apply multiple groups of different normal stresses to the grouped specimens for direct shear test; S7: Obtain the point cloud data of the fracture surface through a specific three-dimensional laser scanner and perform three-dimensional digital reconstruction of the fracture surface; S8: Analyze the point cloud data of the fracture surface and obtain the two-dimensional roughness JRC of the fracture surface; S9: Establish a fracture surface morphology map based on the point cloud data of the fracture surface and determine the arithmetic mean height (S a ), Root Mean Square Deviation (S q ), skewness (S sk ), steepness (S ku ), interface expansion area ratio (S dr ) parameters to quantitatively describe the statistics, mechanism and height distribution characteristics of the fracture surface; S10: analyze the correlation between the two-dimensional and three-dimensional roughness of the fracture surface; S11: determine the relationship between the fracture surface roughness and its stress; S12: determine the phyllite failure mode by combining the fracture surface roughness, high-speed camera fracture process, and PFC numerical simulation.
[0008] Further, in said S1, said There are 9 standard cylindrical specimens for uniaxial compression test and 15 cylindrical specimens of φ25mm×50mm for direct shear test.
[0009] Furthermore, in S2, the sample in the phyllite test is black in color and has obvious stratification. The density of the rock in a dry state is measured to be 2.639 g / cm -3 , the density in its natural state is 2.652g / cm -3 The composition of the rock sample was determined by X-ray diffractometer. The main components of the rock sample were 40.7% calcite, 24.7% quartz, 15.8% chlorite, 9.0% plagioclase, 7.9% muscovite, 1.1% potassium feldspar and 0.8% pyrite.
[0010] Furthermore, in S3, in the uniaxial compression test, the carbonaceous phyllite has low strength and high brittleness, and the post-peak curve drops rapidly. The failure form of the phyllite is shear failure, and the specimen forms a relatively complete fracture surface, and secondary cracks approximately parallel to the axial direction appear.
[0011] Furthermore, in S4, the high-speed camera observes the entire process including the development and expansion of microcracks until the formation of the main fracture surface, and makes a one-to-one correspondence between the destruction process and the stress-strain curve.
[0012] Furthermore, in S5, the numerical simulation gradually adjusts the parameter size by trial and error method, so that the obtained stress-strain curve is close to the stress-strain curve obtained in the physical experiment. When the compressive strength and elastic modulus of the two are close and the macroscopic failure form is similar, the constructed numerical model can be considered to be established. In order to facilitate comparison with the indoor test results, the size of the numerical simulation sample adopts the size of the indoor test sample φ50mm×100mm (diameter×height). The contact model between particles uses a linear stiffness model, and a total of 20,830 particles are generated. After the particles are formed, the connection between the particles is established.
[0013] Furthermore, in S6, the direct shear test uses a microcomputer-controlled rock direct shear apparatus, and divides 15 rock samples into 5 groups, with 3 samples in each group. The test tangential shear force is displacement controlled, the loading rate is 0.2 mm / min, the stress levels are 0.50, 0.75, 1.00, 1.5 and 2 MPa, respectively, and each group of samples is numbered according to a specific rule.
[0014] Furthermore, in S7, the three-dimensional digital reconstruction of the fracture surface uses a handheld three-dimensional laser scanner to scan the fracture surface of the rock, with a scanning area of 275×250 mm and an accuracy of 0.03 mm. The point cloud information of the fracture surface of the rock sample is obtained and a point cloud file in the ".st l" format is generated, and then the point cloud file is imported into the Geomagic Control software analysis system to reconstruct the rock fracture surface.
[0015] Furthermore, in the S8, the two-dimensional roughness calculation cuts the fracture surface into roughness curves, extracts them and numbers them in sequence, calculates the first-order root mean square Z2 parameter of each morphology curve, and determines the two-dimensional roughness value JRC of the fracture surface.
[0016] Furthermore, in S9, the three-dimensional roughness calculation is performed by using the least squares plane fitting method to establish a three-dimensional evaluation reference plane in the same manner as the method for establishing the two-dimensional evaluation centerline. Assume that the straight-line distance from any point on the three-dimensional fracture surface to the reference plane is z(x, y), where x and y represent the projection coordinates of the point on the plane.
[0017] Furthermore, in S10, the correlation between the two-dimensional and three-dimensional roughness of the fracture surface is calculated by constructing the root mean square parameter of the slope of the two-dimensional curve of the fracture surface profile for the fracture surface of the same sample, and by constructing a three-dimensional evaluation reference plane of the fracture surface for the fracture surface of the same sample to calculate the straight-line distance from any point on the three-dimensional fracture surface to the reference plane, so as to determine the three-dimensional roughness S a , S q , S sk , S ku , S dr , and analyze their correlation.
[0018] Furthermore, in S11, the three-dimensional quantitative characterization constructs a plane through the Matlab program to obtain the steepness of the fracture scanning surface as roughness evaluation data, and the JRC value and steepness of the phyllite shear surface change with the normal stress and show a specific regularity. The JRC value and stress are exponentially related, with a correlation coefficient of 0.99, and the compressive stress and the shear surface inclination angle are logarithmically correlated, with a correlation coefficient of 0.99.
[0019] Furthermore, in S12, the rock failure modes include rock failure modes dominated by tensile failure, tensile-shear mixed failure, and shear failure.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. This research method comprehensively grasps the basic characteristics and composition of phyllite by conducting systematic physical and mechanical property tests on phyllite, including density, water absorption rate and X-ray diffraction analysis. This helps to have a clear understanding of the overall properties of phyllite in the early stages of the project and provide basic data support for subsequent engineering design. For example, in tunnel engineering, support structures and construction processes can be reasonably selected based on these data to avoid insufficient support or over-design due to lack of understanding of rock properties, thereby effectively controlling engineering costs and improving engineering safety;
[0022] 2. Use a universal press to conduct uniaxial compression tests on rocks and observe the fracture process with a high-speed camera to clarify the strength characteristics and fracture characteristics of carbonaceous phyllite, and conduct a detailed analysis of the stress-strain curve during the test to clarify the mechanical properties and failure characteristics of phyllite. This enables engineers to accurately predict the possible failure modes of phyllite based on actual projects, such as tunnel projects containing phyllite, and use targeted tunnel lining structures such as anchor rods, anchor cables, and steel supports to strengthen the tunnel bottom surrounding rock structure when the tunnel encounters water-bearing faults and phyllite formations, ensuring the safety of tunnel construction and operation;
[0023] 3. Computer-controlled rock direct shear tests were conducted, with multiple groups of different normal stress levels set. The stress-strain curves during the test were carefully analyzed to clarify the shear failure forms and mechanical property evolution laws of phyllite under different normal stresses. This enables engineers to accurately predict the possible failure modes of phyllite based on the stress conditions in actual projects, and take targeted reinforcement or protection measures in advance. For example, in slope projects, for phyllite areas that may be subjected to large normal stresses, appropriate anti-slip structures can be designed based on the characteristics of wear and shear failure to enhance slope stability and reduce the risk of geological disasters such as landslides.
[0024] 4. The roughness of the phyllite fracture surface was quantitatively characterized from two-dimensional and three-dimensional perspectives, and an accurate relationship model between the JRC value, steepness and normal stress was established, and the failure mode of the phyllite formation under different stress paths was determined. This provides a key parameter basis for engineering numerical simulation and can significantly improve the accuracy of numerical simulation of the mechanical behavior of phyllite. In the numerical simulation analysis of geotechnical engineering, accurate roughness parameters can make the simulation results closer to the actual situation, thereby providing a more reliable reference for the optimization of engineering solutions, helping to improve the scientificity and rationality of engineering design and ensure the smooth implementation of the project. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Figure 1 shows a method for determining the roughness and failure mode of phyllite fracture surfaces based on digital 3D reconstruction.
[0026] Figure 2 In a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction, the X-ray diffraction pattern of phyllite in Yunling Tunnel was detected by Smart Lab SEX diffractometer;
[0027] Figure 3 The stress-strain curves of phyllite under different normal stresses in a research method for determining the roughness of the fracture surface and failure mode of phyllite based on digital three-dimensional reconstruction;
[0028] Figure 4 A schematic diagram of the numerical simulation of a sample in a research method for determining the roughness and failure mode of the fracture surface of phyllite based on digital three-dimensional reconstruction;
[0029] Figure 5 This is a linear fitting diagram of the shear strength and normal stress on the shear failure surface of the sample in a research method for determining the roughness and failure mode of the phyllite fracture surface based on digital three-dimensional reconstruction;
[0030] Figure 6 Crack morphology diagram of samples 5-2 and 5-3 in a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction;
[0031] Figure 7 This is a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction. The numerical simulation fracture failure diagram of phyllite;
[0032] Figure 8 This is a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction. The SEM magnified 2000 times the bedding map of the rock sample;
[0033] Fig. 9A top view of shear failure of phyllite in a research method for determining the roughness of the fracture surface and failure mode of phyllite based on digital three-dimensional reconstruction;
[0034] Fig.10 In a research method for determining the roughness and failure mode of phyllite fracture surface based on digital 3D reconstruction, a handheld 3D scanner was used to collect data images;
[0035] Fig.11 A point cloud data morphology diagram of Table 4 in a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction;
[0036] Fig.12 A JRC quantitative evaluation principle diagram for a research method to determine the roughness and failure mode of phyllite fracture surface based on digital 3D reconstruction;
[0037] Fig.13 A schematic diagram of the Matlab structural plane in a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction;
[0038] Fig.14 A stress-JRC numerical relationship diagram in a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction;
[0039] Fig.15 A stress-fracture surface steepness relationship diagram in a research method for determining the roughness of the fracture surface and failure mode of phyllite based on digital three-dimensional reconstruction;
[0040] Fig.16 A normal stress-JRC-steepness relationship diagram in a research method for determining the roughness and failure mode of phyllite fracture surface based on digital 3D reconstruction;
[0041] Fig.17 This is a flow chart of a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] See also Figure 1-Figure 17 The present invention provides a technical solution: a research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction, comprising:
[0044] 1 Characteristics of Phyllite Surrounding Rocks:
[0045] 1.1 Phyllite physical and mechanical properties:
[0046] The raw stones were collected on site, and the black carbonaceous phyllite cores of Yunling Tunnel were processed into φ25mm×50mm cylinders ( Figure 1 ), processed as Standard cylindrical specimen for uniaxial compression test ( Figure 2 ), and density and water absorption, see Table 1:
[0047] Table 1 Experimental results of some parameters of phyllite
[0048]
[0049] The phyllite in Yunling Tunnel was tested by Smart Lab SEX diffractometer and analyzed by X-ray diffraction pattern (see Figure 2 ), the main components of the rock sample are calcite 40.7%, quartz 24.7%, chlorite 15.8%, plagioclase 9.0%, muscovite 7.9%, potassium feldspar 1.1% and pyrite 0.8%.
[0050] 1.2 Uniaxial compression test of phyllite soft rock:
[0051] A universal material testing machine was selected as the loading device, with a maximum axial force of 100KN. The test was controlled by displacement loading, and the loading rate was 0.1mm / s. Figure 3 ), carbonaceous phyllite has low strength and high brittleness, and the post-peak curve drops rapidly. The strength of the sample has a certain degree of discreteness, which is related to the coring position and the phyllite bedding angle.
[0052] 1.3 Numerical simulation of uniaxial compression test of phyllite soft rock:
[0053] The numerical simulation gradually adjusts the parameters through trial and error to make the obtained stress-strain curve close to the stress-strain curve obtained from the physical experiment. When the compressive strength and elastic modulus of the two are close and the macroscopic failure form is similar, the constructed numerical model can be considered to be established. In order to facilitate comparison with the indoor test results, the size of the numerical simulation specimen adopts the size of the indoor test specimen φ50mm×100mm (diameter×height). The contact model between particles uses the linear stiffness model. A total of 20,830 particles are generated. After the particles are formed, the connection between the particles is established (see Figure 4 ).
[0054] 1.4 Phyllite soft rock direct shear test:
[0055] Using a YZW30-LT2 microcomputer-controlled rock direct shear apparatus, 15 complete rock samples were divided into 5 groups, each with 3 samples, and rock direct shear tests were performed using different normal stresses. During the test, the tangential shear force was displacement controlled, and the loading rate was 0.2mm / min. A total of 5 groups of stress levels (=0.50, 0.75, 1.00, 1.5 and 2MPa) were set. The mechanical properties of phyllite were characterized by stress-strain curves. The experimental data were processed to obtain the stress-strain curves of phyllite under different normal stresses ( Figure 5 ). The shear strength of the experimental phyllite increases with the increase of normal stress, and there is a linear positive correlation.
[0056] 2Analysis of the phyllite fracture process:
[0057] 2.1 Uniaxial compression test fracture analysis:
[0058] Rock fracture diagram (see Figure 6 ). The failure mode of phyllite is shear failure. The specimen forms an integral fracture surface and secondary cracks approximately parallel to the axial direction appear.
[0059] 2.2 Numerical simulation of rupture analysis of uniaxial compression test:
[0060] In numerical simulation, as the strain of phyllite increases, the cracks slowly expand, and the connection and convergence of internal microscopic damage eventually cause macroscopic through-breakage of the material, especially before and after the peak strength, the crack expansion is very rapid and obvious, and the main form of rupture is flaking, and particles can be seen scattered outward from the model (see Figure 7 ).
[0061] 2.3 Microscopic characteristics of shear failure:
[0062] The fragments of the fracture surface of the phyllite were scanned using a field emission scanning electron microscope (SEM) of model Nova NanoSEM400. The scanning results of the fracture surface of the phyllite are shown in the figure below. Figure 8 , magnification is 2000 times.
[0063] 2.4 Macroscopic fracture analysis of phyllite soft rock direct shear test:
[0064] The shear failure process of soft rock joints is mainly sliding, wear and shearing. Fig. 9 ).
[0065] 3. Analysis of fracture surface roughness:
[0066] The macroscopic manifestation of the fracture surface morphology is closely related to the microscopic deformation characteristics. The evaluation indicators are selected from two-dimensional and three-dimensional perspectives: JRC measurement and steepness acquisition, and the relationship between fracture surface roughness and normal stress is analyzed.
[0067] 3.1 Acquisition of fracture surface morphology features:
[0068] In order to deeply analyze the roughness of the rock fracture surface, the ZGScan717 handheld 3D laser scanner scanned the fracture surface of the phyllite (see Fig.10 ). After processing, a three-dimensional digital reconstruction image with the same morphological features as the original fracture surface can be obtained, such as Fig.11 As shown:
[0069] 3.2 Quantitative characterization of two-dimensional roughness:
[0070] The fracture surface roughness was quantitatively evaluated by calculating the JRC value by constructing the slope root mean square (Z2) parameter of the fracture surface profile two-dimensional curve. Fig.12 :
[0071]
[0072] JRC = 32.2 + 32.47 * lgZ2;
[0073]
[0074] Where: L0 is the projection length of the structural surface topography curve in the horizontal direction of the X-axis;
[0075] N is the number of sampling points on the topography curve;
[0076] X i+1 , Z i is the horizontal and vertical coordinate value of the i-th sampling point.
[0077] 3.3 Quantitative characterization of three-dimensional roughness:
[0078] The three-dimensional roughness is determined by constructing a three-dimensional evaluation reference surface for the fracture surface and calculating the straight-line distance from any point on the three-dimensional fracture surface to the reference surface. Fig.13 :
[0079] (1) Root mean square roughness (S q ):
[0080] It is expressed as the offset of the fracture surface contour, which focuses more on reflecting the degree of difference between the elevation points of the fracture surface.
[0081]
[0082] (2) Skewness (S sk ):
[0083] It characterizes the asymmetry of the fracture surface morphology compared to the mean line distribution and is a measure of the fracture surface profile distribution. sk = 0, indicating that the roughness of the contour peak and the contour valley is very similar, showing that the texture of the upper and lower surfaces of the fracture surface is almost symmetrically distributed; when Ssk When S <0, it indicates that the contour valley is rougher than the contour peak, which is manifested in the three-dimensional image as more deep valleys on the fracture surface contour. sk When >0, it indicates that the contour peak is rougher than the contour valley, which is manifested in the three-dimensional image as more peaks on the fracture surface contour.
[0084]
[0085] (3) Steepness (S ku ):
[0086] Evaluate the steepness of the fracture surface profile distribution curve relative to the normal distribution surface shape, S ku The larger the value, the sharper the fracture surface. ku =3, the deviation of the fracture surface morphology satisfies the ideal random normal distribution; when S ku When S >3, it means that the amplitude distribution of the fracture surface profile is relatively steep, and it is a peak-shaped surface; when S ku When <3, it means that the amplitude distribution of the fracture surface contour is relatively flat, which is a low-peak surface.
[0087]
[0088] Where: N is the total number of scanning points on the fracture surface; Z(x i ,y i ) is the straight-line distance from any point on the three-dimensional fracture surface to the reference plane; m and n represent the number of coordinate points in the x and y directions, respectively.
[0089] (4) Interface expansion area ratio (S dr ):
[0090] Evaluate the structural surface roughness, which is defined as the ratio of the fracture surface area to the projection area of the fracture surface on the XOY plane. The calculation method is as follows:
[0091]
[0092] 3.4 Comparison of 2D and 3D roughness of fracture surface:
[0093] Comparison of two-dimensional and three-dimensional fracture surface morphology features, the deflection S sk , steepness S ku , interface expansion area ratio S dr As the independent variable, the two-dimensional roughness JRC was used as the dependent variable for linear regression analysis, and the model formula was obtained.
[0094] The two-dimensional roughness JRC and the three-dimensional fracture surface roughness steepness S ku In contrast, the increasing trends of steepness and JRC with the increase of normal stress are roughly the same.
[0095] 4 Analysis of phyllite failure characteristics:
[0096] 4.1 Relationship between fracture surface roughness and strength characteristics:
[0097] The JRC value of phyllite and stress are exponentially related, and the correlation coefficient is 0.99, indicating a good fitting effect. Fig.14 It can be seen that with the increase of normal stress, the JRC value increases accordingly, and the slope of the fitting curve increases continuously, indicating that the JRC increase rate has an obvious increasing trend.
[0098] from Fig.15 It is easy to see that when the compressive stress is in the range of 0-0.8MPa, the steepness first increases slowly with the increase of compressive stress. When the compressive stress is in the range of 0.8-1.5MPa, the steepness increases significantly. Then, the steepness is still positively correlated with the positive pressure, but the rate of increase decreases significantly, and the slope is close to 0.
[0099] Depend on Fig.16 It can be clearly seen that the steepness and JRC have roughly the same increasing trend with the increase of normal stress. However, the steepness is more acute when the normal stress is 2MPa, indicating that the rock fracture surface is steeper and has more peaks.
[0100] 4.2 Analysis of phyllite failure mode:
[0101] In order to analyze the microscopic connection of the fracture surface morphology in more depth, the three-dimensional steepness, two-dimensional JRC parameters and normal stress were analyzed. In the uniaxial compression test of phyllite, under the initial low stress state, the microcracks inside the rock began to initiate and expand. As the stress increased, the microcracks rapidly expanded and connected with each other, resulting in the intensification of local damage to the rock structure, which made the steepness of the fracture surface increase continuously, the roughness increased, and the failure form was mostly longitudinal penetration. In the direct shear test, phyllite was mainly dominated by sliding and wear damage under low stress, and the interaction between particles was mainly manifested as relatively slow dislocation and friction. From a macroscopic perspective, it presented a relatively regular and slightly undulating form. When the normal stress increased, the phyllite gradually transitioned to the wear and shear failure mode. From a macroscopic perspective, it was manifested as an increase in the overall inclination of the fracture surface, obvious undulations and irregularities, and the steepness and roughness of the shear surface increased accordingly.
[0102] In summary:
[0103] (1) The rock failure mechanism and form will be different under different strain percentage states. Phyllite will produce different failure forms when subjected to uniaxial compression tests and direct shear tests under different normal stress conditions. Numerical simulation can reproduce the failure process from a microscopic perspective and combine it with a macroscopic perspective to better analyze the phyllite fracture process.
[0104] (2) There are two methods for quantitative characterization of fracture surface roughness: two-dimensional and three-dimensional. Data is obtained by fracture surface morphology and processed to obtain the deflection S. sk , steepness S ku , interface expansion area ratio S dr The model formula with two-dimensional roughness JRC as the independent variable and two-dimensional roughness JRC and three-dimensional fracture surface roughness steepness S ku By comparison, the results show that the increasing trends of steepness and JRC with the increase of normal stress are roughly the same.
[0105] (3) There is a significant exponential relationship between the JRC value of phyllite and stress. This exponential relationship provides a strong theoretical basis for accurately predicting the roughness of the fracture surface of phyllite under different stress conditions, which helps to more accurately evaluate and control the mechanical behavior of phyllite in engineering practice.
[0106] There is a complex and close internal relationship among steepness, JRC and normal stress. Grasping these internal relationships is a factor that needs to be considered in engineering applications to ensure the stability and safety of engineering structures.
Claims
1. A research method for determining the roughness and failure mode of phyllite fracture surface based on digital three-dimensional reconstruction, characterized by: The following steps are involved: S1: Collect specific phyllite rough stone processing samples; S2: Determination of physical properties of phyllite test; S3: Determination of uniaxial compressive strength of phyllite test; S4: Observation of the uniaxial compression failure process of rock by high-speed camera; S5: Use PFC3D to establish a numerical model of the uniaxial compression test of rock and analyze the rock fracture characteristics; S6: Use a microcomputer-controlled rock direct shear apparatus to apply multiple groups of different normal stresses to the grouped specimens for direct shear tests; S7: Acquire the point cloud data of the fracture surface through a specific three-dimensional laser scanner to perform three-dimensional digital reconstruction of the fracture surface; S8: Analyze the point cloud data of the fracture surface to obtain the two-dimensional roughness JRC of the fracture surface; S9: Analyze the point cloud data of the fracture surface and determine the three-dimensional roughness of the fracture surface using the arithmetic mean height (S a ), Root Mean Square Deviation (S q ), skewness (S sk ), steepness (S ku ), interface expansion area ratio (S dr ) parameters, which quantitatively describe the statistical, mechanism and height distribution characteristics of the fracture surface; S10: Analysis of the correlation between the two-dimensional and three-dimensional roughness of the fracture surface; S11: Determine the relationship between fracture surface roughness and its stress; S12: Determine the failure mode of phyllite by combining fracture surface roughness, high-speed video recording of the fracture process, and PFC numerical simulation.
2. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In S3, the high-speed camera uses a WP-UT230 ultra-high-speed 150FPS miniature industrial camera to record the entire test process. The camera is up to 150 frames per second at 2.3 million pixels. The test process uses full resolution (1920×1200) and 10 frames per second (FPS).
3. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In S5, the numerical experiment uses the particle flow program PFC3D to construct a uniaxial compression model of the phyllite sample, and analyzes the rock fracture characteristics by comparing the experimental and simulated results of peak strength, elastic modulus, etc.
4. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In S6, the direct shear test uses a microcomputer-controlled rock direct shear apparatus, divides 15 rock samples into 5 groups, and the test tangential shear force uses displacement control, the loading rate is 0.2 mm / min, and each group of samples has a specific numbering rule.
5. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In S7, the three-dimensional digital reconstruction of the fracture surface adopts a three-dimensional laser scanner to obtain the fracture surface point cloud data, and utilizes the principle of laser ranging to quickly reconstruct the three-dimensional model of the measured target and various drawing data such as lines, surfaces, and bodies by recording the three-dimensional coordinates, reflectivity, and texture information of a large number of dense points on the surface of the measured object.
6. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction according to claim 1, characterized in that: In S8, the two-dimensional roughness is calculated by constructing the root mean square parameter of the slope of the two-dimensional curve of the fracture surface profile to calculate the JRC value, and the calculation formula includes the projection length of the structural surface morphology curve in the horizontal direction of the X-axis, the number of sampling points and the horizontal and vertical coordinate values of the sampling points.
7. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In S9, the three-dimensional roughness evaluation is performed by using the arithmetic mean height (S a ), Root Mean Square Deviation (S q ), skewness (S sk ), steepness (S ku ), interface expansion area ratio (S dr ) parameters to quantitatively describe the statistical, mechanistic and height distribution characteristics of the fracture surface.
8. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In S10, the correlation between the two-dimensional and three-dimensional roughness of the fracture surface is calculated for the fracture surface of the same sample, and its two-dimensional roughness JRC and three-dimensional roughness S are calculated respectively. a , S q , S sk , S ku , S dr , and analyze their correlation.
9. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In the S11, the three-dimensional quantitative characterization constructs a plane through a Matlab program to obtain the steepness of the fracture scanning surface as roughness evaluation data.
10. A research method for determining the roughness of the fracture surface and the failure mode of phyllite based on digital three-dimensional reconstruction as claimed in claim 1, characterized in that: In S12, the two-dimensional and three-dimensional roughness of the phyllite, the direct shear test strength and deformation analysis, and the PFC3D microcrack development are comprehensively considered to determine the phyllite failure mode.
Citation Information
Cited By
Method for rapidly acquiring in-situ structural plane characteristics and comprehensively testing influence of in-situ structural plane characteristics on rock mechanical characteristics
CN121612209A
In-situ structural plane feature rapid acquisition and its influence on rock mechanics property comprehensive test method
CN121612209B